2009
DOI: 10.1037/a0017002
|View full text |Cite
|
Sign up to set email alerts
|

Do personality problems improve during psychodynamic supportive–expressive psychotherapy? Secondary outcome results from a randomized controlled trial for psychiatric outpatients with personality disorders.

Abstract: Studies involving patients with personality disorders (PD) have not focused on improvement of core aspects of the PD. This paper examines changes in quality of object relations, interpersonal problems, psychological mindedness, and personality traits in a sample of 156 patients with DSM-IV PD diagnoses being randomized to either manualized or non manualized dynamic psychotherapy. Effect sizes adjusted for symptomatic change and reliable change indices were calculated. We found that both treatments were equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 86 publications
(125 reference statements)
0
10
0
3
Order By: Relevance
“…As modalidades de psicoterapia avaliadas foram: psicoterapia psicodinâmica -PP (Lilliengren et al, 2015;Berghout e Zevalkink, 2009); psicoterapia psicodinâmica de curto prazo -PPCP (Leichsenring et al, 2014;Amianto et al, 2011); psicoterapia psicodinâ-mica de longo prazo -PPLP (Leichsenring et al, 2014;Arvidsson et al, 2011); psicoterapia psicodinâmica intensiva e curto prazo -PPI-CP (Solbakken e Abbass, 2015); psicoterapia psicodinâmica intensiva -PPI (Abass et al, 2015); psicoterapia psicodinâmica de apoio -PPA (Driessen et al, 2013); psicoterapia psicodinâmica breve -PPB (Amianto et al, 2011); psicoterapia psicodinâmica focal -PPF (Zipfel et al, 2014); tratamento comunitário de foco psicodinâmico -TCFP (Vinnars et al, 2009); psicoterapia psicodinâmica interpessoal -PIT (Sattel et al, 2012); psicoterapia psicodinâmica pela internet -PPIN (Johansson et al, 2013); psicanálise -PA (Grande et al, 2009); psicaná-lise com predomínio de interpretações transferências -PAT e sem interpretações transferenciais -PAST (Høglend et al, 2008) e terapia cognitivo comportamental -TCC; (Levi et al, 2015;Zipfel et al, 2014); terapia cognitivo comportamental pela internet -TCCI (Johansson et al, 2013); terapia do esquema -TE (Gude e Hoffart., 2008); terapia de apoio -TA (Vinnars et al, 2009); e, terapia focal -TF (Heinonen et al, 2012). Foram encontradas também intervenções com medicamentos como a fluoxetina (Sørensen et al, 2011), sozinhos ou combinados com psicoterapia psicodinâmica (Koppers et al, 2011); e também intervenções combinadas com outros tratamentos multidisciplinares, tais como dieta alimentar e acompanhamento familiar (Abba-te Daga et al, 2015).…”
Section: Modalidades De Psicoterapiaunclassified
See 2 more Smart Citations
“…As modalidades de psicoterapia avaliadas foram: psicoterapia psicodinâmica -PP (Lilliengren et al, 2015;Berghout e Zevalkink, 2009); psicoterapia psicodinâmica de curto prazo -PPCP (Leichsenring et al, 2014;Amianto et al, 2011); psicoterapia psicodinâ-mica de longo prazo -PPLP (Leichsenring et al, 2014;Arvidsson et al, 2011); psicoterapia psicodinâmica intensiva e curto prazo -PPI-CP (Solbakken e Abbass, 2015); psicoterapia psicodinâmica intensiva -PPI (Abass et al, 2015); psicoterapia psicodinâmica de apoio -PPA (Driessen et al, 2013); psicoterapia psicodinâmica breve -PPB (Amianto et al, 2011); psicoterapia psicodinâmica focal -PPF (Zipfel et al, 2014); tratamento comunitário de foco psicodinâmico -TCFP (Vinnars et al, 2009); psicoterapia psicodinâmica interpessoal -PIT (Sattel et al, 2012); psicoterapia psicodinâmica pela internet -PPIN (Johansson et al, 2013); psicanálise -PA (Grande et al, 2009); psicaná-lise com predomínio de interpretações transferências -PAT e sem interpretações transferenciais -PAST (Høglend et al, 2008) e terapia cognitivo comportamental -TCC; (Levi et al, 2015;Zipfel et al, 2014); terapia cognitivo comportamental pela internet -TCCI (Johansson et al, 2013); terapia do esquema -TE (Gude e Hoffart., 2008); terapia de apoio -TA (Vinnars et al, 2009); e, terapia focal -TF (Heinonen et al, 2012). Foram encontradas também intervenções com medicamentos como a fluoxetina (Sørensen et al, 2011), sozinhos ou combinados com psicoterapia psicodinâmica (Koppers et al, 2011); e também intervenções combinadas com outros tratamentos multidisciplinares, tais como dieta alimentar e acompanhamento familiar (Abba-te Daga et al, 2015).…”
Section: Modalidades De Psicoterapiaunclassified
“…Outro método utilizado para complementar os questionários foram entrevistas presenciais semiestruturadas desenvolvidas para o próprio estudo, ou entrevistas estruturadas, por exemplo: Operationalized Psychodynamic Diagnosis -OPD Task Force (Levi et al,2015;Vinnars et al, 2009;Marttunen et al, 2008;Johansson et al, 2013;Kronström et al, 2009;Koppers et al, 2011;Høglend et al, 2008;Gude e Hoffart, 2008;Abbate-Daga et al, 2015;Berghout e Zevalkink, 2009;Lilliengren et al, 2015;Grande et al, 2009;Arvidson et al, 2011;Leichsenring et al, 2014). O estudo que avaliou custo-efetividade dos serviços de saúde também utilizou, além dos questionários, os registros nacionais de verificação para compor as medidas de follow-up (Abass et al, 2015).…”
Section: Métodos E Medidas Utilizados No Follow-upunclassified
See 1 more Smart Citation
“…Previously, the KAPP has been used in psychosomatic research (ulcerative colitis, [11]; adult atopic dermatitis [12]), in personality disorder research (personality change after brain injury [13]); in borderline and organic personality disorder [14], in psychotherapy research [15][16][17][18]; and in substance abuse research [19,20]. Only one previous study has, however, examined the KAPP profile of patients with eating disorders [21], and the sample size in that study was quite small (n = 16) and consisted of both patients with AN (n = 7) and BN (n = 9).…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that improvements extending beyond the end of treatment can be attained in many aspects of personality functioning, e.g. quality of object relations and interpersonal problems, reflecting quality and extent of characteristic behavior patterns (Vinnars et al, 2009), and defense mechanisms (Bond and Perry, 2004;Perry and Bond, 2012). Instead, comparisons between various short-term therapies have mostly found no significant differences across different outcome domains for patients with depressive and anxiety disorder (Abbass et al, 2011;Cuijpers et al, 2010;Driessen et al, 2013;Salzer et al, 2011;Slavin-Mulford and Hilsenroth, 2011), albeit some studies have shown lesser (Leichsenring et al, 2013b;Watzke et al, 2012) and some greater (Kallestad et al, 2010) effects in different aspects of personality functioning after short-term psychodynamic therapy in comparison to other therapies.…”
mentioning
confidence: 99%